Assessment of noise levels generated in swine production units in Ibadan, Nigeria (2012)
The increase in pork consumption globally in recent times has led to a corresponding increase in pig production with more people being employed in the industry to provide the needed services. Pigs are known to generate a lot of noise which could constitute a potential health hazard and against which remedial measures must be taken. The establishment of the levels of noise generated in piggery production units and their possible consequences on the workers in such units was the main objective of this study. The research execution consisted of a simple survey among piggery workers to obtain information relevant to noise generation and effect; and physical measurement of the levels of noise generated in selected piggery farms in Ibadan, Nigeria. The survey revealed that workers spend between 3-6 hours daily within the units and wear no noise protective devices. The levels of noise generated in the farms ranged from 95-103 dB (A) and especially during feeding period and other activities. The duration of these noises which are mainly intermittent ranged from 30 to 150 minutes. These levels of noise and the periods for which they last are above the maximum levels of 99 dB (A) over a period of 19 and 140 minutes specified by NIOSH and OSHA respectively. Swine workers in Ibadan, Nigeria are exposed to excessive occupational noise hazards and remedial measures are desirable in order to protect them. The provision of Personal Hearing Protective Devices (PHPDs), adequate medical check-ups as well as use of personal noise dosimeters for the swine workers and good housing structures and facilities for the animals are recommended.